Hearing in Drosophila Requires TilB, a Conserved Protein Associated With Ciliary Motility. - Kavlie, R.G.; Kernan, M.J.; Eberl, D.F. (Genetics, 2010)
Cilia were present in the earliest eukaryotic ancestor and underlie many biological processes ranging from cell motility and propulsion of extracellular fluids to sensory physiology. We investigated the contribution of the touch insensitive larva B (tilB) gene to cilia function in Drosophila melanogaster. Mutants of tilB exhibit dysfunction in sperm flagella and ciliated dendrites of chordotonal organs that mediate hearing and larval touch sensitivity. Mutant sperm axonemes as well as sensory neuron dendrites of Johnston's organ, the fly's auditory organ, lack dynein arms. Through deficiency mapping and sequencing candidate genes, we identified tilB mutations in the annotated gene CG14620. A genomic CG14620 transgene rescued deafness and male sterility of tilB mutants. TilB is a 395-amino-acid protein with a conserved N-terminal leucine-rich repeat region at residues 16-164 and a coiled-coil domain at residues 171-191. A tilB-Gal4 transgene driving fluorescently tagged TilB proteins elicits cytoplasmic expression in embryonic chordotonal organs, in Johnston's organ, and in sperm flagella. TilB does not appear to affect tubulin polyglutamylation or polyglycylation. The phenotypes and expression of tilB indicate function in cilia construction or maintenance, but not in intraflagellar transport. This is also consistent with phylogenetic association of tilB homologs with presence of genes encoding axonemal dynein arm components. Further elucidation of tilB functional mechanisms will provide greater understanding of cilia function and will facilitate understanding ciliary diseases.